Comparison of Knowledge, Attitude and Practice of Isfahan Dental Students about Chlorhexidine, Liseterine and Fluoride Mouthwashes - Mohammad Khosravi; Shirin Amini Sedeh; Hajar Shekarchizadeh; Ali Ahmadi (Isfahan University of Medical Sciences, 2023)
Dentists play an important role in improving the society knowledge regarding the use mouthwashes. Therefore, such knowledge is necessary during the dental education. The aim of this research is to evaluate students' knowledge, attitude and performance regarding the use of mouthwash among the students of Islamic Azad University at Isfahan as well as a comparison between free and state university students.Materials & Methods:In this descriptive-cross sectional study, a valid and reliable researcher designed questionnaire including 26 question was distributed among 134 Azad university dental student of different level (basic sciences, fifth year and senior year) and senior students of Isfahan medical science dental school. one-way ANOVA, T-test, Shapiro-Wilk, Tukey and Pearson Correlation Coefficient tests served for statistically analyze (α = 0.05(.Results:A significant difference exists between knowledge, attitude and performance of basic sciences, fifth year and senior year. However, there was no significant relationship between knowledge and attitude, knowledge and performance, attitude and performance of different educational levels.No significant difference also reveals between the mean score of knowledge, attitude and performance of the students of the two universities.Conclusion:The results showed an improvement in knowledge, attitude and performance at the student by the level of education. However, knowledge and performance remained at a moderate level. Also, raising awareness does not necessarily lead to good attitudes and performance